A SURVEY OF MEDICINAL PLANTS USED BY KAVIRAJES OF CHALNA AREA, KHULNA DISTRICT, BANGLADESH - Rahmatullah, Mohammed; Ferdausi, Dilara; Mollik, Md. Ariful Haque; Jahan, Rownak; Chowdhury, Majeedul H.; Haque, Wahid Mozammel Haque1 Mozammel (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
Kavirajes or traditional medicinal practitioners form the primary healthcare providers of the predominantly rural population of Bangladesh. Kavirajes use a variety of medicinal plants for treatment of different ailments. The formulations prepared from medicinal plants vary considerably between Kavirajes of different regions of the country. The objective of this study was to conduct an ethnomedicinal survey amongst the Kavirajes of Chalna area, Khulna district, Bangladesh. That area is known to contain a diversity of medicinal plants. Information on 50 plant species was obtained. These medicinal plants belonged to 49 genera and 33 families. Twenty five plants were used to treat skin diseases and twenty three plants for treatment of intestinal tract disorders, which included constipation, indigestion, stomachache, diarrhea, and dysentery. Fourteen plants were also used by the Kavirajes to treat cancer or tumor. Nine plants were used as insecticide, eight for rheumatoid arthritis, and seven for wounds. Five plants were used to treat jaundice. Five plants were also utilized to treat animal and snake bites, which included tiger bites. Six plants were used to treat diabetes, and two each for the treatment of leprosy, and sexually transmitted diseases like gonorrhea. Five plants were used to treat impotency, while one plant was used as an abortifacient. Three plants were used to treat helminthiasis, which we found to be quite common amongst the population, while four plants were used to treat heart disorders. Taken together, these plant species offer considerable potential for discovery of novel compounds of pharmacological interest